KEMAMPUAN ACTIVITY DAILY LIVING PADA PASIEN PASCA STROKE: LITERATURE RIVIEW - Mega Sartika Lumbantoruan; Wasisto Utomo; Reni Zulfitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Stroke is a condition and arises due to a circulatory disorder in the brain that causes brain tissue death, resulting in paralysis or death, therefore post-stroke sufferers depend heavily on fulfilling ADL because of their limited motion. This limitation causes stroke patients to depend on their family or other people to fulfill their basic needs for activities.This study used a literature review design. Search research journals using Google Scholar with the keyword Activity of Daily Living Ability in Post-Stroke patients. Results: There were five articles that fit the inclusion criteria followed by a matrix analysis based on the objectives, methods, samples, research results, and similarities and differences. The results of the literature review show that the ADL ability of post-stroke patients is independent. The ability of daily living activity in post-stroke patients affects the lives of post-stroke patients.Keywords: Ability, Activity of Daily Living, Pasca Stroke